1994
DOI: 10.1093/ajcp/102.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Features of Kimura’s Disease in Fine-needle Aspirates:A Study of Eight Cases

Abstract: Kimura's disease is a chronic inflammatory disorder of unknown etiology, presenting usually as painless subcutaneous swellings in the head and neck region or in the salivary glands. The cytologic features of fine-needle aspirates of eight cases of Kimura's disease were studied with reference to the histologic appearance of the subsequent surgical specimens. In the cytologic smears, the prominent feature was the presence of significant numbers of eosinophils in a background of lymphoid cells. Fragments of colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…FNAB is a safe and highly accurate procedure and should be considered for the initial assessment of a parotid mass. The case presented here, in which the affected structures were two intraparotid lymph nodes and not the salivary gland parenchyma, is comparable with case 7 in the Chow et al [23] series and with the well-documented observation reported by Jensen [25]. In our case, however, diagnosis and management were based on the FNAB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…FNAB is a safe and highly accurate procedure and should be considered for the initial assessment of a parotid mass. The case presented here, in which the affected structures were two intraparotid lymph nodes and not the salivary gland parenchyma, is comparable with case 7 in the Chow et al [23] series and with the well-documented observation reported by Jensen [25]. In our case, however, diagnosis and management were based on the FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…Eosinophils and isolated granules interspersed within the cytological smear are often very numerous; sometimes sparse polykaryocytes are also detectable. Fragments of collagenous sclerotic tissue may be noted here and there [23].…”
Section: Discussionmentioning
confidence: 74%
“…It is often diagnosed in male patients. [15] Although, IPT is placed within the neoplastic category, it is best-regarded as a morphologic entity showing mainly inflammatory cells with a pleomorphic spindle cell component mimicking a tumor. The term, "pseudotumor" is appropriate, and as the atypical spindle cells are myofibroblastic, it can be termed as an inflammatory myofibroblastic tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphoid population consisted of a mixture of small and large lymphocytes and immunoblasts, representing the corresponding distinctive histologic finding of lymphoid follicles with germinal centers. 4 Occasionally WF-type giant cells, which are actually polykaryocytes, were seen. Although the presence of these giant cells has been considered an important diagnostic feature by many authors, 14,18 others have not documented their presence, nor is it necessary for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although it has been reported in the Eastern literature, 13,29 there are very few reports on the cytology of Kimura's disease; only four cytologic reports appear in the English-language literature. 3,4,14,18 Described initially by Kimura, followed by Kim, Szeto and Kung, these lesions tend to occur in the head and neck region as subcutaneous masses, especially in the preauricular region, often affecting the salivary glands and adjacent muscles. 1,9,17,22,24 Regional lymph nodes are usually involved, with accompanying raised IgE levels in the serum and peripheral blood eosinophilia.…”
mentioning
confidence: 99%